PENGARUH KUALITAS PELAYANAN PENDIDIKAN TERHADAP KEPUASAN DAN LOYALITAS PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS MEDAN AREA MEDAN - LUBIS, ADELINA (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2014)
The problem of the research were how the influencing of service quality on studentâs satisfaction and to identify how the influencing of studentâs satisfaction on studentâs loyalty in Faculty Economy of Medan Area University. The method of data collection were interview, questionare and study of documentation. The model of data analysis used are multiple linear regression analysis and simple linear regression analysis. The determination of sample usingÂ  Slovin formula and the writer used the accidental sampling, the total samples were 95 people.The result of this research were service quality which consists of tangibles, reliability, responsiveness, assurance and empathy worked together to gave significant contribute of service. The result of second hypothesis through t test shows that studentâs satisfaction significantly influence studentâs loyalty.